2.5D imaging: obtaining depth information from 2D helium-beam radiographs - Metzner, Margareta; Schlechter, Annika; Zhevachevska, Daria; Schlegel, Patrice; Jäkel, Oliver; Martišíková, Mária; Gehrke, Tim (Physics in medicine and biology, 2025)
Objective. Ion-beam radiography has been proposed as a daily on-couch imaging modality for ion-beam radiotherapy range verification. However, an ion-beam radiograph only contains 2D information since it shows a projection of the patient along the beam direction. To extract depth information of anatomical changes from 2D helium-beam radiographs, we experimentally investigated the 2.5D imaging approach. Approach. At the Heidelberg ion-beam therapy center, we acquired helium-beam radiographs of a homogeneous plastic phantom and an anthropomorphic phantom. We changed the geometry of both phantoms to mimic anatomical changes and acquired data before and after the change. After reconstructing plane-of-interest difference images along depth in 1 mm steps, we analyzed the spatial resolution by means of the slanted edge approach and a method based on a median filter and Tenengrad focus measure. The depth of the maximum spatial resolution was then compared to the one where the change was introduced in the experiment and their difference was determined as measure of accuracy. Main results. For both the slanted edge and Tenengrad method, all accuracy values of the plastic phantom were below 11 mm. Furthermore, the found depth values of all but one gap position coincided with the ground truth position of the edge within the 2 σ uncertainty. In the anthropomorphic phantom, we reached a depth accuracy of mm. Significance. The 2.5D imaging approach, which was investigated experimentally for the first time in this work, offers a technique to estimate the depth of an anatomical change based on the acquisition of 2D ion-beam radiographs. This information is crucial to determine whether the change is located within the treatment field and thus impairs the treatment. 2.5D ion-beam radiography could therefore be used for daily on-couch imaging to monitor the anatomy of the patient and make ion-beam radiotherapy treatments more precise.